2020
DOI: 10.1038/s41598-020-65000-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of 1 + PRN and 3 + Q3M regimens of intravitreal conbercept injection for exudative age-related macular degeneration

Abstract: This retrospective study aimed to analyze the clinical outcomes of two regimens of intravitreal injections of conbercept [1+pro re nata (PRN) and 3 + Q3M] for the therapy of exudative age-related macular degeneration (AMD). In total, 105 eyes diagnosed with exudative AMD were enrolled. The eyes in the 1+PRN group (n = 51) received intravitreal injection of conbercept one time, followed by PRN retreatment. The eyes in the 3 + Q3M group (n = 54) received intravitreal injection of conbercept on three consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…However, in China, these two anti-VEGF drugs were not approved by health insurance for use in patients with wAMD until May 2019. Prior to this date, the large cost of high-priced drugs greatly affected the patient's treatment compliance and compromised data integrity ( 32 , 33 ). Therefore, the anti-VEGF treatment regimen and its efficacy in wAMD patients in China before 2019 were different from the data reported worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…However, in China, these two anti-VEGF drugs were not approved by health insurance for use in patients with wAMD until May 2019. Prior to this date, the large cost of high-priced drugs greatly affected the patient's treatment compliance and compromised data integrity ( 32 , 33 ). Therefore, the anti-VEGF treatment regimen and its efficacy in wAMD patients in China before 2019 were different from the data reported worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…The BCVA was evaluated at baseline and at 1, 3, and 12mo after the intravitreal injection. The BCVA was assess by The Early Treatment Diabetic Retinopathy Study (ETDRS) vision acuity chart at four meters of distance [13] . Central Retinal Thickness The CRT between the macular fovea to the Bruch membrane was detected by optical coherence tomography (OCT; Heidelberg, Germany) at baseline and 1, 3, and 12mo after conbercept treatment.…”
Section: Best-corrected Vision Acuitymentioning
confidence: 99%
“…Conbercept is an anti-VEGF agent which was manufactured by Chengdu Kanghong Biotech Co., Ltd., China. It is an engineered fusion protein yielded by the gene recombination of VEGF receptor (VEGFR)-1 and VEGFR-2 with the Fc fragment of human immunoglobulin, which can bind VEGF-A, VEGF-B, and placental growth factor (PLGF) and has successfully improved best-corrected visual acuity (BCVA) and central retinal thickness (CRT) in the patients with CNV [12][13][14] . It was reported that conbercept significantly decreased serum VEGF levels at one day and one week after treatment, and this side effect did not sustain for one month [15] .…”
Section: Introductionmentioning
confidence: 99%
“…The patients with nAMD, which is featured by choroidal neovascularization (CNV), lead to severe and fast vision impairment. Intravitreal injection of anti‐vascular endothelial growth factor (VEGF) agents, such as conbercept [4], have been generally and effectively used worldwide in the clinical treatment of nAMD via targeting CNV. It has been revealed that anti‐VEGF therapy improves vision and quality of life for nAMD patients [5].…”
Section: Introductionmentioning
confidence: 99%